PENGARUH MEDIA SOSIAL DAN WORD OF MOUTH TERHADAP LOYALITAS PELANGGAN MELALUI KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING PADA KAFE GUNUNG WALAT - Rian Permana; Yulianingsih Yulianingsih; Awa Awa (Politeknik Negeri Ambon, 2026)
Introduction: This study aimed to examine the effects of social media and word of mouth on customer loyalty, with customer satisfaction serving as a mediating variable, at Kafe Gunung Walat.Methods: This study employed a quantitative approach using a descriptive and verificative research design. The sample consisted of 100 customers of Kafe Gunung Walat selected through an accidental sampling technique. Data were collected using a structured questionnaire and analyzed with IBM SPSS Statistics version 25. The analytical procedures included validity and reliability tests, classical assumption tests, path analysis, hypothesis testing, coefficient of determination analysis, and the Sobel test to examine the mediating effect of customer satisfaction.Results: The findings revealed that social media and word of mouth had a positive and significant effect on customer satisfaction. In addition, social media, word of mouth, and customer satisfaction positively and significantly influenced customer loyalty. Customer satisfaction was also found to mediate the relationship between social media and customer loyalty, as well as between word of mouth and customer loyalty. These findings indicate that effective social media utilization and positive word of mouth communication contribute to higher customer satisfaction, which subsequently strengthens customer loyalty toward Kafe Gunung Walat. Keywords: customer loyalty; customer satisfaction; social media; word of mouth.